Kepemimpinan Transformasional Kepala Madrasah Berbasis Gender: (Studi Kasus di MAN Insan Cendekia OKI) - Muh Sobari; Saipul Annur; Mukti Ali (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
This study aims to analyze the implementation of gender-based transformational leadership of the madrasah principal at MAN Insan Cendekia OKI, examine the perceptions of male and female teachers, and identify the challenges and its impact on teacher performance and the school work climate. This research employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the interactive model of Miles and Huberman. The findings indicate that the principal’s leadership is implemented in a participatory, collaborative, and inclusive manner by providing equal opportunities for teachers without gender bias. Teachers’ perceptions are generally positive, although differences emerge between relational and structural emphases. The challenges include gender stereotypes, adaptation to participatory leadership patterns, and differing understandings of gender equality. The implementation of this leadership approach contributes to improved teacher motivation and performance, as well as the creation of an inclusive and conducive work climate. This study contributes to the development of Islamic educational management by offering a contextual and applicable perspective on gender-based transformational leadership.